Diderot's rocaille jewel: an example of rococo humour - Ibeas-Altamira, Manuel Juan (Romanica Olomucensia, 2019)
Was Denis Diderot, the philosopher of Langres, a humorist? The idea may seem surprising, considering the popular assumption that the philosophers of the European Enlightenment, in which Diderot played a primary role, had a very serious plan. Diderot occupies a unique position within the history of literature, and is often cited as both a genius and the first truly modern writer: outstandingly, humour plays a fundamental role in this consideration. The object of this study is the libertine novel Les Bijoux Indiscrets (The Indiscreet Jewels in English), the most mysterious of his creations. This paper analyses the artist's experience of humour, his originality, and his comic opinions about the social and political events of his day portrayed in this story. The subject matter of his rococo fiction veers from dreamlike to grotesque, documentary to imaginary, humorous to harshly satirical: the different features that differentiate his work will be explored. This research proves that women occupy a central place within Diderot's œuvre and in this text particularly, especially through portraying women in possession of their own powers, whether political or sexual. Diderot notes that in almost every nation Nature and the laws have combined in a way that is cruel to women. That is why he decides to write about their most unknown feelings and thoughts using a truly comic situation. It might be concluded that he typifies women as being relentless in love and ruthless in hate, but with a superlative might, and throughout all of it playing with a sensitive rococo style.
Keywords: literature; humour; Enlightenment; Diderot; rococo; women